THE CORRELATION BETWEEN LINGUISTIC INTELLIGENT AND STUDENTS ABILITY IN WRITING DESCRIPTIVE TEXT - Indah Lestari; Rudha Widagsa (Universitas Duta Bangsa Surakarta, 2022)
The role of linguistic intelligent in learning a foreign language particularly in writing skill has received increased attention across a number of disciplines in recent years. This study aims to investigate the correlation between linguistic intelligence and students' ability to write descriptive texts. This quantitative research was conducted at a vocational high school in Central Java, Indonesia in January 2022. The data was collected through a questionnaire instrument and a descriptive text writing test of 80 samples from 394 populations. The data analysis technique employed product moment and descriptive analysis using SPSS. The result of the study shows the significance value obtained from the product moment correlation = 0.528 and the significance value 0.000 < probability 0.05, which means the hypothesis (H0) was rejected and the hypothesis in this study (Ha) was accepted. Based on the statistical analysis, this study concluded that there was a correlation between students’ linguistic intelligence and the ability of writing descriptive text.